Synthesis of Cyclodextrin Inclusion Complexes with (η-Cyclopentadienyl)iron Derivatives as Potential Nonlinear Optics Materials - Teixeira, António P. S. (2012)
Dicarbonyl( h5 -cyclopentadienyl)iron tetrafluoroborates containing aromatic nitriles as ligands were synthesized. These and other ( h5 -cyclopentadienyl)iron derivatives were used to obtain intercalation compounds with b -cyclodextrin.